Overview of descriptive epidemiology and types of COVID-19 cluster transmission at Puskesmas Sentolo I in 2020-2021 - Susilaningsih, Tutik Inayah (BKM Public Health and Community Medicine, 2021)
Objective: The aim of this study was to find out the epidemiological description and types of Covid-19 cluster transmission at Puskesmas Sentolo I until May 2021. Contents: Descriptive of epidemiological analysis was used in this study from the daily data and the report of epidemiological investigation of Covid-19 cases. During the period March 2020 until May 2021, the amount of Covid-19 cases at Puskesmas Sentolo I tend to increase every month. Covid-19 cases were very highest in April 2021 especially at Kalurahan Sentolo up to 40.3%. The higher incidence of case was in the female group than the male (54%). The age group of 46-59 years old has 30.9% as the highest rank and the least cases in the 0-5 years group only 1.7%. Percentage of rapid antibody test comparison to PCR as a gold standar reached 57% especially on IgM examination detected. Case Fatality Rate (CFR) of Covid-19 at Puskesmas Sentolo I was 2.9% with comorbid such as diabetes mellitus, hypertension, stroke, and obesity. Types of cluster transmission was mostly at the family cluster up to 59% of the total cases (31 family clusters). If the cluster transmission of Covid-19 in the family could be prevented and detected early, it was possible that Puskesmas Sentolo I just had 40% of the total Covid-19 cases without any household transmission. This required multi stake holders collaboration.